Lavagem de dinheiro e a imputação das ações neutras - Melo, Matheus Barbosa (2018)
The present study seeks to analyze the relationship of neutral actions to the crimes of money laundering in the country. The diversity of the problems in this area led to the division of the theme into three chapters, with the common purpose of ascertaining questions related to some cases created in the last and fourth chapter, whose situations involve the professional labor and incidence of money laundering law. In order to do so, (I) at the beginning, it follows the construction of the necessary bases for the evaluation and determination of the traditional criteria of imputation in a legitimate criminal law, observing the legislative options adopted by the Brazilian legislator, in view of the modern perspectives of the functionalism of risk, already adjusting it to the current criminal law function in this country. (II) After establishing the doctrinal premises adopted, the theme of neutral actions is presented, under four different approaches, namely: a) the concept of neutral actions; b) the problem involved and its verification in dogmatic; c) the main solutions of doctrine; d) posture to be taken. (III) Next, a study on the money laundering law is outlined, with considerations about the criminal type and its preventive measures. (IV) In the fourth chapter, an approach is given to some practical cases, involving money-laundering, in order to test all the content presented in the previous chapters, with the purpose of verifying if, in fact, it is possible to occur neutrality in the imputation related to money laundering. Finally, a conclusive synthesis is presented